CELLULAR AND TISSUE DIFFERENTIATION PROCESSES IN HUMAN EMBRYONIC DEVELOPMENT - Ismailov Diorbek Shakhobiddin ogli; Absaidov Elburis Takhir ogli; Haitov Bekmurod Bahrom ogli (Western European Studies, 2025)
This article provides a systematic analysis of the processes of cellular and tissue differentiation occurring during human embryonic development. From a cytological perspective, it examines the cleavage of the zygote, the formation of blastomeres, and their morphological and functional specialization. Furthermore, the formation of various tissue types — epithelial, connective, muscular, and nervous — during gastrulation and organogenesis is described from a histological standpoint. The embryological analysis highlights the interrelations between the three germ layers — ectoderm, mesoderm, and endoderm — and the organs and tissues derived from them. The article contributes to a deeper understanding of the complex step-by-step processes of embryonic development at the cellular and tissue levels and serves as a theoretical foundation for studying the early stages of human ontogenesis.
Keywords: Embryonic development; cellular differentiation; tissue differentiation